2021
DOI: 10.3389/fpsyg.2021.709570
|View full text |Cite
|
Sign up to set email alerts
|

Positive and Negative Emotional Eating Are Not the Same—The Spanish Version of the Positive-Negative Emotional Eating Scale (PNEES)

Abstract: The literature points to the importance of distinguishing between positive and negative emotional eating in relation to overeating and binge eating. The aim of this study was to evaluate the Spanish version of the Positive-Negative Emotional Eating Scale (PNEES) in a Spanish community sample. The sample consisted of 628 participants. The mean age was 27.5 (SD = 12.7) and 70.1% of them were women. The participants completed the PNEES, and measures of anxiety and depression (HADS), and eating disorder-related sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…(2021) found a low incidence of abdominal obesity among positive emotional eaters. Manchón et al. (2021) and Howells et al.…”
Section: Discussionmentioning
confidence: 99%
“…(2021) found a low incidence of abdominal obesity among positive emotional eaters. Manchón et al. (2021) and Howells et al.…”
Section: Discussionmentioning
confidence: 99%
“…Emotional eating (EE) is an eating disorder that involves increased eating in response to negative emotions. However, EE was initially defined as eating only in response to negative emotions [ 1 ]. Several studies have shown that a positive mood can also lead to an increase in food intake, which is also a reaction towards food cravings in response to stress or negative emotions (such as anxiety, anger, depression and loneliness) as an attempt to alleviate these concerning states [ 2 ].…”
Section: Introductionmentioning
confidence: 99%